Una mirada al posconcilio en España - Sebastián Aguilar, Fernando (Estudios eclesiásticos, 2006)
As a significant member of the Spanish Episcopate, which undertook the task of implementing the Second Vatican Council in Spain, the author reviews the history of Spanish Catholic Church and the documents issued by the Bishops Conference during these last decades; and shows the lights and the shadows of that process. Finally, some new tasks are proposed to the Catholic Church in Spain, both regarding its inner life and its relationship to Spanish Society.